Awareness on prevention of coronavirus (Covid-19): a case study of internships students in Universiti Teknologi MARA Cawangan Negeri Sembilan / Syafiqah Samat ... [et al.] - Samat, Syafiqah; Ghazali, Nurdia Azlin; Mohd Razali, Nur Hidayah; Idris, Noor Aisyah (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Corona-virus disease or also known as Covid-19 is a viral disease that highly infectious for the respiratory system and is caused by novel severe acute respiratory syndrome Corona-virus 2 (SARS-CoV-2). It had been found started from Wuhan City, Hubei Province, China in December 2019 and keep spreading extremely fast all over the world since then. In Malaysia, the first Covid-19 case was confirmed on 25th January 2020 and still ongoing until nowadays. Due to the previous pandemic outbreak, every country in the world put complete lock down that affect the economy, trade, tourism and others industries which also included the education sector. Education sector went through many changes that give a great impact on students, educational institutes and teachers. According to Dani et al. (2020), due to the lock down that government do in order to control the pandemic spread, many institutes and students have to make changes in their education plans. In order to lessen the chances to get infect are everybody plays an important role to take care of themselves especially people who have to work during pandemic that will be include internship students. According to Elhadi et al. (2020), they are expected to have knowledge and awareness as compared to the public since they are at a higher risk of transmission since they have to work with other people. In order to make sure that they have a small chance to get the transmission, they have to always practice the preventive measures. As Covid-19 continues to spread across the country and the world, we all must be observant. We have to change our routines and daily life even though it were extremely hard, because these changes are extremely important for now and in the future. As stated by National Center for Immunization and Respiratory Diseases (NCIRD) and Division of Viral Diseases in 2020, people will be safer when they can take more steps on prevention measures in order to slow down the spread of Covid-19. Everyone plays an important role to stop the spread of this new and dangerous virus.